Is raphe only an innocent bystander finding or a predictor of complications in bicuspid aortic valve patients? Experience of Italian REBECCA registry. (25th November 2020) - Bellino, M; Citro, R; La Carrubba, S; Fabiani, I; Faggiano, P; Desseni, N; Faganello, G; Barbieri, A; Cresti, A; Moreo, A; Dentamaro, I; Monte, I; et al.
Abstract: Background: Bicuspid aortic valve (BAV) is the most common congenital heart disease, affecting 0.5%–2% of the general population. It is associated with valvular dysfunction (aortic stenosis and/or regurgitation, endocarditis) but also with a wide spectrum of aortopathy with unpredictable clinical presentations. The role of the raphe is still controversial. Methods: The REgistro della Valvola Aortica Bicuspide della Società Italiana di ECocardiografia e CArdiovascular Imaging is a retrospective/prospective, multicenter, observational registry, with definitive diagnosis of BAV. Anamnestic, demographic, clinical, and instrumental data are collected into dedicated software at first evaluation and during follow-up. Aortopathy was defined as: annulus ≥14 mm/m 2 ; root ≥20 mm/m 2 ; sino-tubular junction (STJ) ≥16 mm/m 2 ; ascending aorta (AA) ≥17 mm/m 2 ; it was classified in: type A, dilation of the ascending aorta; type B, dilation of the aortic root and the ascending aorta; and type C, isolated dilation of the aortic root. Patients were divided in two groups; those with raphe and those without. Results: At December 2019, 800 patients with BAV (Male, 73.3%; M:F ratio 2.9; Mean Age at diagnosis 44±23 years) have been included in the registry. Prevalence of hypertension was 29%, diabetes mellitus 3%, smoking-habit 8%. We reported a majority (42.7%, 342) of patients with type 1, followed by type 2 (10.2%, 82) and type 3 (3.7%, 30). No gender differences were observed according to BAV phenotypes, while male gender was associated to higher prevalence of aortic valve regurgitation (p=0.0003). Moreover, in patients with raphe, aortic stenosis (49.8% vs 38.4%; p=0.014) and aortopathy (57.4% vs 46.1%; p=0.034) were significantly prevalent (see Table 1). Of note no difference about aortic regurgitation (62.8% vs 48.7%; p=0.064) between two groups were detected. At univariable logistic regression analysis the presence of raphe was significantly associated with aortopathy [OR: 1.57; 95% CI: 1.02–1.42; p=0.037] especially with Type B Aortopathy [OR: 0.55: 95% CI: 0.33–0.93: p=0.02]. Conclusion: Preliminary data from Italian Multicenter REBECCA registry highlight that, in patients with BAV, the raphe is not an innocent bystander but a risk factor for aortic stenosis and type B aortopathy. Funding Acknowledgement: Type of funding source: None